2013
DOI: 10.5101/nbe.v5i2.p76-85
|View full text |Cite
|
Sign up to set email alerts
|

Low Concentration Platinum Nanoparticles Effectively Scavenge Reactive Oxygen Species in Rat Skeletal L6 Cells

Abstract: Prolonged exposure to excessive reactive oxygen species (ROS) increases risk factors for many diseases. Therefore, elimination of ROS as well as prevention of its production becomes critically important. In the present study, we evaluated the levels of cytotoxicity and ROS scavenging activity induced by synthetic platinum nanoparticles (PtNPs). Average size of synthesized PtNPs was 2.2 nm. Synthetic PtNPs were found to scavenge both induced and endogenous H 2 O 2 significantly in L6 rat skeletal muscle cells a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…Pt nanoparticles exhibit protective effects that are attributed to their suppressing ROS production caused by UV-light-induced epidermal inflammation [69] . Synthetic Pt nanoparticles have been shown to scavenge ROS in cultured HeLa cells [70] , to induce expression of antioxidant enzyme genes in rat skeletal muscle L6 cells [71] , and to act as an SOD/catalase mimetic agent in human lymphoma cells [72] . Model ERW prepared from NaCl, KCl or NaOH solutions has been shown to exert beneficial effects such as anti-diabetic, anti-cancer, and life-span extension of nematodes because of its ROS scavenging ability in numerous in vitro and in vivo studies [73] [78] .…”
Section: Discussionmentioning
confidence: 99%
“…Pt nanoparticles exhibit protective effects that are attributed to their suppressing ROS production caused by UV-light-induced epidermal inflammation [69] . Synthetic Pt nanoparticles have been shown to scavenge ROS in cultured HeLa cells [70] , to induce expression of antioxidant enzyme genes in rat skeletal muscle L6 cells [71] , and to act as an SOD/catalase mimetic agent in human lymphoma cells [72] . Model ERW prepared from NaCl, KCl or NaOH solutions has been shown to exert beneficial effects such as anti-diabetic, anti-cancer, and life-span extension of nematodes because of its ROS scavenging ability in numerous in vitro and in vivo studies [73] [78] .…”
Section: Discussionmentioning
confidence: 99%
“…Dissolved hydrogen molecules diffused in cells have been shown to reduce intracellular hydroxyl radicals [ 78 , 79 ]. Pt Nps have been shown to be taken up by pinocytosis, diffusion, and other processes and act as novel ROS scavengers in vitro and in vivo [ 80 , 81 ]. Internalized functional components are capable of scavenging ROS produced by cytotoxic stimuli such as H 2 O 2 , SNP, and glutamate used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The non-cytotoxic properties of Pt NPs have been reported in previous research. All these studies showed that 10 -4 -10 3 ng/cm 2 (7.86×10 -7 -7.86 mg/l) of 20-100 nm Pt NPs affected neither the cellular metabolism nor cell death [33]. Moreover, hybrids nanomaterials have been broadly invented.…”
Section: Nanozymes Role In Cytoprotectionmentioning
confidence: 99%
“…Moreover, hybrids nanomaterials have been broadly invented. Graphene oxide [33] nanomaterials broadly use in research, due to their high conductivity, absorbing properties, large surface area, and outstanding biocompatibility [34].…”
Section: Nanozymes Role In Cytoprotectionmentioning
confidence: 99%